Teknik Cetak Resin Dalam Pembuatan Sarana Upakara Pengabenan Dan Petulangan Di Rugos Art & Casting: Resin Printing in the Production of Ritual Offerings for Cremation at Rugos Art & Casting - i dewa, gede adikresna; Dana, I Nnyoman; Agung Jaya CK, I Gusti Ngurah (Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
The human body is enlivened by the soul, allowing the body to move and function in this universe. When the soul leaves the human body, that is when a person dies. The relatives and family feel the loss, and thus, a form of respect is carried out through a ceremony, according to the customs, beliefs, or religion of the deceased. In general, the Balinese people, who are predominantly Hindu, conduct a burial ceremony. Ngaben is a cremation ceremony aimed at expediting the return of the elements present in the human body (earth, fire, water, air, and space) to their original state. The Ngaben ceremony requires certain facilities such as offerings for the ceremony and a structure called